You are here : connecting flights - Oh, Ellen (Allida, 2023)
An incident with the TSA in an overcrowded Chicago airport brings twelve Asian American teens and young adults--hitherto strangers to each other--together. As their journeys intertwine, these twelve Asian Americans learn new challenges of friendship, of being younger siblings, how powerful words really are, and, in the end, how significant a blue Stratocaster electric guitar really can be.